HUBUNGAN KEBIASAAN MENGKONSUMSI JUNK FOOD DENGAN KEJADIAN HIPERTENSI PADA REMAJA DI SMA NEGERI 01 KUDUS - Silviana S, Andhike; Maryanto, Sugeng (UNIVERSITAS NGUDI WALUYO, 2013)
The prevalence of hypertension on adolescences is increasing, one contributing factor is the eating habit in adolescences. They prefer to eat food and snacks as junk food. This study aimed to determine the relationship between junk food consumption habits and the incidences of hypertension on adolescences. The study design was cross-sectional study with the samples of 95 people taken by using cluster sampling method. The determination of hypertension on adolescences used the standard of NHANES. The measurement of blood pressure used a sphygmomanometer, height used microtoise, and eating habit used semi-quantitative FFQ. The data analysis used SPSS. Bivariate correlation analysis used chi-square test (Î± = 0.0500). The results showed that most respondents rarely ate junk food that were equal to 85.3% (n = 81), most of them had enough fat intake which where equal to 76.8% (n = 73), and enough sodium as much as 94.7 % (n = 90). There was a relation between the frequency of junk food consumption with the incidences of hypertension (p = 0.000). There was a relation between excessive fat intake with the incidences of hypertension (0.001). There is a relation between excessive sodium intake (0.002) and the incidences of hypertension. Conclusion: There was a significant association between the consumption of junk food consumption habits with the incidences of hypertension in adolescences. Abtrak : Prevalensi hipertensi remaja semakin meningkat, salah satu faktor penyebabnya adalah kebiasaan makan pada remaja. Remaja lebih memilih kudapan dan jajan seperti junk food. Penelitian ini bertujuan untuk mengetahui hubungan antara kebiasaan konsumsi junk food dengan kejadian hipertensi pada remaja. Rancangan penelitian ini adalah cros-sectional dengan jumlah sampel 95 orang diambil dengan metode cluster sampling. Penentuan hipertensi pada remaja menggunakan standar dari NHANES. Pengukuran tekanan darah dengan menggunakan Sphygmomanometer, tinggi badan menggunakan microtoise, dan kebiasaan makan menggunakan FFQ semi-kuantitative. Analisis data menggunakan SPSS. Analisis bivariat menggunakan uji korelasi chi-square (Î±=0,05) Hasil penelitian menunjukkan bahwa sebagian besar responden jarang mengonsumsi junk food yaitu sebesar 85,3% (n=81), sebagian besar mempunyai asupan lemak cukup yaitu sebesar 76,8% (n= 73), dan natrium cukup sebesar 94,7% (n= 90). Ada hubungan antara frekuensi konsumsi junk food dengan kejadian hipertensi (p = 0,000). Ada hubungan antara asupan lemak berlebih dengan kejadian hipertensi (0,001). Ada hubungan antara asupan natrium berlebih (0,002) dengan kejadian hipertensi. Ada hubungan yang bermakna antara kebiasaan konsumsi junk food dengan kejadian hipertensi pada remaja.